Type I and Ir pleuropulmonary blastoma (PPB): A report from the International PPB/DICER1 Registry. Issue 4 (20th December 2022) - Nelson, Alexander T.; Harris, Anne K.; Watson, Dave; Miniati, Doug; Finch, Mike; Kamihara, Junne; Mitchell, Sarah G.; Wilson, David B.; Gettinger, Katie; Rangaswami, Arun A.; Campos, José M.; Lederman, Sara; et al.
Abstract: Background: Pleuropulmonary blastoma (PPB) is the most common lung cancer of infancy and early childhood. Type I PPB is a purely cystic lesion that has a microscopic population of primitive small cells with or without rhabdomyoblastic features and may progress to type II or III PPB, whereas type Ir lacks primitive small cells. Methods: Children with suspected PPB were enrolled in the International PPB/ DICER1 Registry. Pathology was centrally reviewed, and follow‐up was ascertained annually. Results: Between 2006 and 2022, 205 children had centrally reviewed type I or Ir PPB; 39% of children with type I and 5% of children with type Ir PPB received chemotherapy. Outcomes were favorable, although 11 children (nine with type I and two with type Ir PPB) experienced progression to type II/III ( n  = 8) or regrowth of type I PPB at the surgical site ( n  = 3), none of whom received chemotherapy before progression. Age and cyst size in combination were more suitable than either factor alone in predicting whether a particular lesion was type I or Ir PPB. Conclusions: For young children with type I PPB, outcomes are favorable, but complete resection is indicated because of the risk for progression. Chemotherapy may be useful in a subset of children at increased risk for recurrence/progression. Efforts to risk stratify children with type I PPB to optimize outcomes while reducing treatment‐related side effects are underway. Abstract : Outcomes for children with type I and Ir pleuropulmonary blastoma (PPB) are favorable, although progression to advanced disease is noted in some children. Chemotherapy may be useful in a subset of children with type I PPB who are at increased risk for recurrence/progression.